Evaluation of Patient Medical Record System Management Based on the Public Health Number 269 Of 2008 at Puskesmas Talise - Irna Baniat; Munir Salham; rosnawati rosnawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
Efforts to achieve a fair and correct medical record management system, containing notes and documents about patient identity, medical examinations, medication, actions, and other services. The type of research used is descriptive with a qualitative approach, using data collection techniques, observation, interviews and documentation, informants' determination using purposive sampling totaling six people, namely, the Head of Talise Health Center 1 person, three medical record officers, and two patients. The results showed that the Standard Operational Procedure (SPO) policy was still in the process of changing the SOP for the medical records section. Human Resources still needed to increase the number of employees with special competence, expertise, and skills in the medical record section. Has not been recorded in the organizational structure. It is recommended that Talise Puskesmas use the Health Metrics Network Evaluation Framework, which is very good in evaluating the medical record system in the Operational Service Standards (SPO), HR, and Organization policies section of these medical records so that it can increase the quality of Puskesmas services and can develop further.